INFLUENCE OF MOTHER’S KNOWLEDGE ABOUT TYPE OF WEANING FOOD ON THE NUTRITIONAL STATUS OF 6-24 MONTHS CHILDREN IN POSYANDU GODAN VILLAGE, TAWANGHARJO - Ratna Sri Rahayu; Sutrisno Sutrisno; Sulistiyarini Sulistiyarini (Universitas An Nuur, 2018)
Background; Nutrition plays an important role in the growthof the child. According to the World Health Organization (2016) 6% or 40,6 million are overfed and 7,7% or 52 million malnourished. Knowledge is one of the internal factors that affect the nutritional status of children (Notoatmodjo, 2007). According to Mulyana (2011), 29 (40,3%) of respondents who have less knowledge have malnourished children. Based on WHO (2007) in Syatriani (2010), 54% ofÂ 11 million children under five around the world die from malnutrition and 46% died due to concomitant diseases such as respiratory infections, diarrhea, malaria and measles.Purpose - To determine the effect of motherâ€™s knowledge about the type of weaning foods on the nutritional status of 6-24 months children in Posyandu Godan Village Sub-District of Tawangharjo.Method; Design research was analytic survey with case control approach with Chi Square test. The population were 132 respondents. Sample collectingused non-probability sampling Quota method. Sample case group were 30 respondents and control groups were 30 respondents.Result; Mothers with good knowledgewho have Â children with bad nutritional status are 9 (15%)Â respondents while mothers with bad knowledge who havechildren with good nutritional status are 21 (35%) respondents. Mothers with good knowledge who have children with good nutritional status are 20 (33,3%) respondents while the mothers with bad knowledge who have children with good nutritional status are 10 (16,7%) respondents. Ï value = 0,010 and 4,667 Odds Ratio value. It means that there is influence of motherâ€™s knowledge about the type of weaning foods on the nutritional status of 6-24 month children in the Godan Village Tawangharjosub-District.Conclusion; There isinfluence of motherâ€™s knowledge about the type of weaning foods on the nutritional status of 6-24 months children in Posyandu Godan Village Sub-District of Tawangharjo.Â Keywords : Nutritional Status, Weaning Food, Knowledge Level